2012
DOI: 10.1111/cmi.12006
|View full text |Cite
|
Sign up to set email alerts
|

Actin-mediated plasma membrane plasticity of the intracellular parasiteTheileria annulata

Abstract: SummaryPathogen-host interactions are modulated at multiple levels by both the pathogen and the host cell. Modulation of host cell functions is particularly intriguing in the case of the intracellular Theileria parasite, which resides as a multinucleated schizont free in the cytosol of the host cell. Direct contact between the schizont plasma membrane and the cytoplasm enables the parasite to affect the function of host cell proteins through direct interaction or through the secretion of regulators. Structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
3
14
0
1
Order By: Relevance
“…This suggests that F-actin is less accessible to exogenously added antibodies after fixation, perhaps due to epitope alterations during fixation or the association of actin binding proteins to filaments. Interestingly, while actin has never been previously associated with this membranous network in T. gondii , it appears very similar to structures recently described for the related parasite Theileria annulata , which was shown to contain F-actin in a similar configuration (Kühni-Boghenbor et al, 2012). …”
Section: Discussionsupporting
confidence: 72%
“…This suggests that F-actin is less accessible to exogenously added antibodies after fixation, perhaps due to epitope alterations during fixation or the association of actin binding proteins to filaments. Interestingly, while actin has never been previously associated with this membranous network in T. gondii , it appears very similar to structures recently described for the related parasite Theileria annulata , which was shown to contain F-actin in a similar configuration (Kühni-Boghenbor et al, 2012). …”
Section: Discussionsupporting
confidence: 72%
“…In addition to the differences we have described in the residues involved in lateral contacts, a candidate responsible for increased stability is residue 200, which is a glycine in Plasmodium actin I and T. gondii actin [69] but serine or threonine in canonical actins as well as Plasmodium actin II and Theileria actin [9], all of which form long filaments. It has been reported that the double mutant G200S/K270M in T. gondii actin leads to an increased filament length when using phalloidin-labeled filaments [69].…”
Section: Discussionmentioning
confidence: 97%
“…Actin polymerization is indispensable for gliding and likely involved in host cell invasion and egress [6][8]. Despite evidence for this crucial role of filamentous actin, long filaments have only been visualized in Theileria [9], which appears not to use actin filaments for host cell invasion [10]. The presence of regular actin filaments in Plasmodium is uncertain [11][13].…”
Section: Introductionmentioning
confidence: 99%
“…Tomography was performed essentially as described before [15,21,23,24,28]. Merozoites in RPMI medium mixed with 10 nm colloidal gold particles were transferred onto glow-discharged holey carbon Quantifoil EM grids.…”
Section: Methodsmentioning
confidence: 99%